INFLUENCE OF ANNEALING ON THE STRUCTURAL AND OPTICAL CHARACTERISTICS OF INDIUM OXIDE THIN FILMS PREPARED USING THERMAL EVAPORATION IN A VACUUM METHOD - A. Hussain, Saleem; Al-Hilo, Eman .A.; Hatem, Alyaa H (JOURNAL OF ADVANCES IN PHYSICS, 2016)
In the work, the structures and the optical parameters were studied for In2O3 thin films Before and after annealing at different temperatures (400 and 500 ) thin films were prepared on glass substrate by by vacuum thermal evaporation. The X-Ray diffraction showed that In2O3, In2O3 Plasticizedthin films which were prepared to have a polycrystalline cubic structure. The most preferential orientation is along the (321) direction for all deposited In2O3 films. Some parameters of the films were calculated as the average grain size and the dislocation density. Optical properties measurement transmittance (T) of the film shows that they have high transmittance (82.7%) is obtained for at annealing 500 . The optical properties such as absorption coefficient (Î±) using the transmittance measurement from an UV-vis spectrophotometer, with a range of wavelength (300-1100) nm. And also calculated energy gap for thin films. and also calculated energy gap for thin films, the result has been shown that the optical energy gap increasing with increasing annealing.